If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(z + -88) = 84 Reorder the terms: 7(-88 + z) = 84 (-88 * 7 + z * 7) = 84 (-616 + 7z) = 84 Solving -616 + 7z = 84 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '616' to each side of the equation. -616 + 616 + 7z = 84 + 616 Combine like terms: -616 + 616 = 0 0 + 7z = 84 + 616 7z = 84 + 616 Combine like terms: 84 + 616 = 700 7z = 700 Divide each side by '7'. z = 100 Simplifying z = 100
| 558.25/14.5 | | 120=6(2x+6) | | 15+8c=95 | | 7i(3-5i)= | | Y+4x=13 | | 6(3x+-4)=12 | | 6(3x/2-x)=6(x/6-2/3) | | 21-(x-5)= | | 2.5(x+6)=75x | | .2(y-3)=-3(y-5) | | 0.33(6x-12)=0 | | 128=2(8x-8)+2x | | 16p^2-8p-3= | | 19(x+19)=x+29 | | 2.75x+3=1.75x+7 | | 78=(-2m+3)+m | | -0.55p-5=0.45p | | 0=2x+1+lnx | | x(3500)+y(2500)=17255 | | (6-4w+4y)(-8)= | | 180/25 | | 10-3(2x-3)=13 | | -4/2-4= | | x(3500)+y(2000)=17255 | | x^2+3*x+4=sqrt(x^2+3*x+5) | | 4y+7=2 | | -12=59.76 | | 4-x=x-24 | | 14y+5=2 | | 3x+2(.5x-x)=4 | | 13/4z=39 | | x/4log10(4x) |